Ultrasound exposure during pregnancy affects rabbit foetal parathyroid hormone (PTH) level - Md. Dom, Sulaiman; Abdul Razak, Hairil Rashmizal; Ahmad Zaiki, Farah Wahida; Saat, Nurul Hidayah; Abd Manan, Khairunnisa; Che Isa, Iza Nurzawani; Hashim, Ummi Farhana (AME Publishing Company, 2013)
The aim of this study was to investigate the changes in parathyroid hormone (PTH) level of rabbit foetal bodies exposed to ultrasound at different gestational stages. A total of 9 pregnant rabbits (Oryctolagus cuniculus) were insonated for 60 minutes at the middle of 1st, 2nd and 3rd gestational stages for group A (n=14 newborns), group B (n=7 newborns ) and group C (n=24 newborns) respectively. Seven pregnant rabbits with 41 newborns severed as negative control group. Blood samples were withdrawn from each newborn rabbits for Parathyroid Hormone-Intact (PTH-I) test. Results of the independent samples t-test implied statistically significant differences (P<0.05) between the control group and the 1st stage (P=0.001), the 2nd stage (P<0.001) and the 3rd stage group (P<0.001). This in-vivo study revealed diagnostic ultrasound heating has the potential of affecting foetal PTH level. This study observed significantly low PTH level for all the treated groups. A further study should be instituted to determine whether this finding in rabbit may also occur in human by means of clinical trials.